Legal Protection of Abortion for Rape Victims - Herni Nursheta Resmi; Yusuf Saefudin (UM Purwokerto Press, 2023)
This study discusses: How is the legal review of the act of abortion as a result of rape based on Law no. 39 of 1999 concerning Health and its Relation to Human Rights, and how is the application of material criminal law by Judges to perpetrators of participation in the crime of abortion. The approach method used in this study is a normative juridical approach. The data collection method in this study was carried out by means of literature study. The data that has been collected, then processed and analyzed using qualitative methods. The results of this study can be concluded that: Rape victims experience unwanted pregnancies not only experience mental and psychological suffering, they also have to seek justice through legal means as a result of their abortions. The Indonesian Criminal Code strictly prohibits all forms of abortion. Whereas Law Number 36 of 2009 concerning Health provides confirmation of legal abortion arrangements, namely the result of medical emergencies and pregnancy as a result of rape. The perpetrator of the abortion as a result of rape is included in the category of unlawful acts or strictly regulated in Article 48 of the Criminal Code that no one can be punished by anyone who commits an act because he was forced by an urgent condition (overmacht). Human rights which are more specific to women's reproductive rights as part of women's human rights are guaranteed to be fulfilled in the Constitution of the Republic of Indonesia jo. Article 49 paragraph (3) of Law Number 39 of 1999 concerning Human Rights states that the special rights attached to women due to their reproductive function are guaranteed and protected by law. Children as victims of rape as well as perpetrators of abortion who are charged with imprisonment will have a negative impact on the mental growth and soul of the child. Based on criminal responsibility explained in the doctrine that the elements seen are the ability to be responsible, there is an element of error, there is no excuse for forgiveness. Rape victims as well as abortion perpetrators, who are clearly victims, instead receive unfair treatment when seeking justice. Children should receive guarantees for normal physical, mental and mental development. Settlement of cases against child victims of rape as well as perpetrators of abortion through the judicial process, the results will give a negative stamp to children as convicts who can adversely affect the community environment.